2007
DOI: 10.1111/j.1399-6576.2007.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Scandinavian Clinical Practice Guidelines on the diagnosis, management and follow‐up of anaphylaxis during anaesthesia*

Abstract: The present approach to the diagnosis, management and follow‐up of anaphylaxis during anaesthesia varies in the Scandinavian countries. The main purpose of these Scandinavian Clinical Practice Guidelines is to increase the awareness about anaphylaxis during anaesthesia amongst anaesthesiologists. It is hoped that increased focus on the subject will lead to prompt diagnosis, rapid and correct treatment, and standardised management of patients with anaphylactic reactions during anaesthesia across Scandinavia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
329
0
26

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(357 citation statements)
references
References 90 publications
2
329
0
26
Order By: Relevance
“…This classification describes four grades of increasing severity: I; cutaneous-mucous signs (e.g. urticaria), II; moderate multivisceral signs (involvement Tachycardia and hypotension are usually observed, though bradycardia (resulting from the Bezold-Jarisch reflex) may occur in up to 10% of cases during general anaesthesia (Dewachter et al 2009, Harper et al 2009, Kroigaard et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…This classification describes four grades of increasing severity: I; cutaneous-mucous signs (e.g. urticaria), II; moderate multivisceral signs (involvement Tachycardia and hypotension are usually observed, though bradycardia (resulting from the Bezold-Jarisch reflex) may occur in up to 10% of cases during general anaesthesia (Dewachter et al 2009, Harper et al 2009, Kroigaard et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Only 173 (54.7%) patients with suspected hypersensitivity reaction referred to our clinic had bloods taken for serum tryptase measurement. An important message to clinicians who refer patients with suspected hypersensitivity reactions is to ensure blood samples are taken for serum tryptase analysis according to recommended time intervals [1][2][3][4]. Indeed, a recent editorial suggested that even more samples should be taken, for example at one, two, three, six, 12 and 24 hours after a reaction, to ensure that at least some of these samples reach the laboratory and demonstrate the rise and fall of serum tryptase concentrations [41].…”
Section: Discussionmentioning
confidence: 99%
“…The referral of patients with suspected hypersensitivity reactions to anaesthetic drugs for further investigations is now considered mandatory, and is the responsibility of the primary anaesthetist involved [2][3][4]. A study from 2005 showed that an informed guess was not a reliable way of determining the cause of a suspected hypersensitivity reaction during anaesthesia, and may put a significant number of patients at unnecessary risk [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the drugs administered during the perioperative period such as antibiotics or NSAIDs will be studied following regular procedures and are not going to be described in this review. However, DPT with perioperative drugs has added several limitations and there is not a consensus procedure for its performance (grade of recommendation, C) [10,145,146]. The final goal is to reach a total dose of the drug needed for anaesthetic induction (propofol, etomidate, ketamine), or during the anaesthetic procedure (opioids, midazolam...).…”
Section: Drug Provocation Testsmentioning
confidence: 99%